The relationship between brand knowledge, satisfaction and loyalty among conference organizers / Zamri Ahmad - Ahmad, Zamri (2014)
Building and properly managing brand equity has become essential for any business organizations, and hospitality organizations are no exception. As such, branding has become one of the most dominant indicators in the global hotel industry performance. Customer-based brand equity is a valuable tool in brand positioning and evaluates their marketing strategy. Necessary feedback can be obtained from consumers for this evaluation will aid in: identifying service or product related problems; identifying advertising/positioning problems; and also providing feedback to the employees on where improvements need to be made. Customer-based brand equity scale gives service industry managers a structured approach for formulating their branding strategies. The purpose of this study was to explore the relationship between the multidimensionality of brand equity (brand knowledge) construct, satisfaction and loyalty in the conference market segment within the hotel industry. In relation to the above purposes, this study was looking at three brand knowledge constructs namely staff service, self-image congruence and brand awareness towards brand satisfaction and attitudinal loyalty by assessing the conference organizers. The target population was among the organizers of conferences held in Penang and Klang Valley. The sample was taken from the conference alert and UiTM conference blast through Lotus Notes system within the duration of May 2013 to October 2013. The numbers of 150 questionnaires were distributed but only 102 were returned and analysed (58 in Klang Valley and 44 in Penang). Series of statistical analyses were employed (IBM SPSS version 20 and AMOS version 20). The model fits well with the data. In this case, the xAsup 2A/df was 1.46 and CFI of .98 indicate a good fit between the hypothetical model and the sample data. The RMSEA for the measurement model was .068. Other fit indices also point to an acceptable model fit between the model and the data (GFI = .90, AGFI = .80, CFI =.98). All four hypotheses were tested and posited a positively significant relationship (brand awareness, staff service, self-image congruence with brand satisfaction and attitudinal loyalty).This study also contributes to the existing brand loyalty studies by assessing the relationship between brand equity and attitudinal brand loyalty in the hospitality industry. It also discusses the theoretical and managerial implications of the findings and the limitation of the study.